Influence of a suspended aid on the amplitude variables of circles on pommel horse - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Suspended aid is a popular device used for learning and refining circles, the most basic skill on pommel horse. The aim of this study was to examine how the use of a suspended aid influences the amplitude variables of circles. Eighteen gymnasts performed three sets of 10 circles with and without a suspended aid, and several kinematic variables identified in literature were analysed. As a result, circles with the aid showed a smaller body flexion angle, a greater shoulder angle, and a greater ankle diameter, although a shoulder diameter remained relatively similar to circles without the aid. Circles with the aid appeared to be more desirable in terms of the movement amplitude. In this sense, a suspended aid could function as spotting, which is often used for a progression to learn gymnastics skills, to let gymnasts experience a desired movement pattern.